Engineered Cementitious Composites for Electrified Roadway in Megacities A Comprehensive Study on Functional Performance - Bawono, Ali Aryo.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book describes the development of an innovative solution for electrified roadway pavements based on engineered cementitious composites, which are exhibiting an extreme tensile strain capacity that is much higher than conventional concrete. This enables the pavement to work without steel reinforcement and to embed a dynamic wireless power transfer technology for charging electric vehicles. At first, the book presents a modified performance-driven design approach to improve the composites to achieve the optimum pavement design in terms of functional and structural performance. It shows that the modified composites can be used to fulfil the safety and comfort factors without neglecting the characteristics of conventional ones. Further, 3D finite element and fluid dynamics models are used to analyse the pavement properties. The validated models can predict the functional performance, including skid resistance, surface water drainage, and noise. In the remaining part of the thesis, an environmentally-friendly photocatalytic function for pavement made of engineered cementitious composites is investigated. In turn, a multi-criteria design analysis is proposed to identify the optimum functional performance of the pavements. All in all, this book reports on a comprehensive approach to design, analyse and optimize engineered cementitious composites for electrified road pavement application. A special emphasis is given on applications in Singapore and other tropical megacities.
Introduction -- Electro-mobility solution towards the ultimate public transport system with a case study of Singapore -- State of the Art: Engineered Cementitious Composites Precast Ultra-Thin Whitetopping (ECC-PUTW) -- State of the Art: Functional Performance of Pavement -- Multi Criteria Decision Analysis on the Functional Performance of Pavement.
Keywords: Engineering design; Transportation engineering; Traffic engineering; Building materials; Engineering Design; Transportation Technology and Traffic Engineering; Structural Materials; Cement composites; Electricity in transportation; Pavements, Composite